The Effect of Obliquity of Slip in Normal Faults on Distribution of Open Fractures - von Hagke, Christoph; Kettermann, Michael; Bitsch, Nicolai; Bücken, Daniel; Weismüller, Christopher; Urai, Janos L. (Frontiers in Earth Science, 2019)
Close to surface, cohesive rocks fail in extension, which results in open fractures that can be several tens of meters wide, so-called massively dilatant faults. These open fractures make fault slip analysis in rifts challenging, as kinematic markers are absent. Faults in rifts often have oblique slip kinematics; however, how the amount of obliquity is expressed in the surface structure of massively dilatant faults remains enigmatic. Furthermore, the structures of oblique dilatant faults at depth is largely unconstrained. To understand the subsurface structures we need to understand how different obliquities of slip influence the surface structures and the corresponding structures at depth. We present analog models of oblique faults using different cohesive materials in a sandbox with adjustable basement fault slip obliquity from 0° to 90°. Experiments with different mean stress and material cohesion were run. Using photogrammetric 3D models, we document the final stage of the experiments and investigate selected faults by excavation. We show that fault geometry and dilatancy changes systematically with angle of obliquity. Connected open fractures occur along the entire fault to a depth of 6-8 cm, and as isolated patches down to the base of the experiments. Using the scaling relationship of our models implies that transition from mode-1 to shear fracturing occurs at depths of 250 – 450 m in nature. Our experiments show the failure mode transition is a complex zone and open voids may still exist at depths of at least 1 km. We apply our results to the dilatant faults in Iceland. We show that the relationship between angle of obliquity and average graben width determined on faults on Iceland matches experimental results. Similarly, fracture orientation with respect to fault obliquity as observed on Iceland and in our experiments is quantitatively comparable. Our results allow evaluation of the structure of massively dilatant faults at depth, where these are not accessible for direct study. Our finding of a complex failure mode transition zone has consequences for our understanding of fracture formation, but also influences our interpretation of fluid flow in rift systems such as magma ascent or flux of hydrothermal waters.